Advertising Effectiveness and Influence of Consumer Buying Decision of LED Television - Uddin, Md. Jamal; Rahman, Md. Mostafizur; Kalam, Abul; Rahman, Md. Ferdush (Asian Business Review, 2019)
The main aim of the present study was to identify the influence of advertising effectiveness on the consumer buying decisions of different brands of ‘LED’ television. The study was descriptive. Five television showrooms in Dinajpur district, Bangladesh (Sony, Singer, Samsung, LG, and Walton) were purposively selected for collecting primary data for this study. The respondents were selected using a convenience sampling method that came to the television showroom for purchasing ‘LED’ television. The primary data for this study were collected through a structured questionnaire. The study result shows that advertisement has a positive effect on consumer buying decisions of ‘LED’ television, Sony brand (p =.000 <0.05) and 43.9% of variation in consumer buying decision has been contributed by advertisement effectiveness. For Singer brand p =.010 <0.05), Samsung brand p =.003 <0.05), LG brand p =.341>0.05) and the null hypothesis is accepted for LG band and Walton brand p =.000 <0.05) and 42.3% of variation in consumer buying decision has been contributed by advertisement effectiveness.